Systematizing Professional Knowledge of Medical Doctors and Teachers: Development of an Interdisciplinary Framework in the Context of Diagnostic Competences - Christian Förtsch; Daniel Sommerhoff; Frank Fischer; Martin R. Fischer; Raimund Girwidz; Andreas Obersteiner; Kristina Reiss; Kathleen Stürmer; Matthias Siebeck; Ralf Schmidmaier; Tina Seidel; Stefan Ufer; et al. (MDPI AG, 2018)
Professional knowledge is highlighted as an important prerequisite of both medical doctors and teachers. Based on recent conceptions of professional knowledge in these fields, knowledge can be differentiated within several aspects. However, these knowledge aspects are currently conceptualized differently across different domains and projects. Thus, this paper describes recent frameworks for professional knowledge in medical and educational sciences, which are then integrated into an interdisciplinary two-dimensional model of professional knowledge that can help to align terminology in both domains and compare research results. The models’ two dimensions differentiate between cognitive types of knowledge and content-related knowledge facets and introduces a terminology for all emerging knowledge aspects. The models’ applicability for medical and educational sciences is demonstrated in the context of diagnosis by describing prototypical diagnostic settings for medical doctors as well as for teachers, which illustrate how the framework can be applied and operationalized in these areas. Subsequently, the role of the different knowledge aspects for acting and the possibility of transfer between different content areas are discussed. In conclusion, a possible extension of the model along a “third dimension„ that focuses on the effects of growing expertise on professional knowledge over time is proposed and issues for further research are outlined.